Purchase Intensity of Halal Cosmetics among Muslim Consumers: A Theory of Consumption Values Approach - Ru'yat, Camelia Erliana; Hayati, Amelia (Share: Jurnal Ekonomi dan Keuangan Islam, 2025)
Given the growing demand for halal cosmetics, understanding the drivers of purchasing behavior among Muslim consumers is essential. This study applies the Theory of Consumption Values (TCV) to examine the purchase intensity of halal cosmetics. The research was conducted among 194 Muslim consumers in the Jakarta Metropolitan Area, Indonesia, a significant market for halal goods. Using a quantitative methodology, survey data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that emotional value exerted the strongest influence on purchase intensity, followed in significance by functional, social, and conditional values. In contrast, epistemic value did not demonstrate a significant impact. These findings provide actionable insights for the halal cosmetics industry, highlighting the importance of developing products and marketing strategies that enhance emotional appeal, showcase functional benefits, leverage social influence, and optimize conditional triggers. Abstrak Intensitas Pembelian Kosmetik Halal di Kalangan Konsumen Muslim: Pendekatan Theory of Consumption Values. Meningkatnya permintaan kosmetik halal di kalangan konsumen Muslim membuat penting untuk memahami faktor-faktor pendorong perilaku pembelian mereka. Studi ini menerapkan Teori Consumption Values (TCV) untuk menguji intensitas pembelian kosmetik halal. Penelitian dilakukan terhadap 194 konsumen Muslim di Wilayah Metropolitan Jakarta, Indonesia, yang merupakan salah satu pasar signifikan untuk produk halal. Menggunakan metodologi kuantitatif, data survei dianalisis dengan Partial Least Squares Structural Equation Modeling (PLS-SEM). Hasil penelitian menunjukkan bahwa nilai emosional memberikan pengaruh terkuat terhadap intensitas pembelian, diikuti secara signifikan oleh nilai fungsional, sosial, dan kondisional. Sebaliknya, nilai epistemik tidak menunjukkan dampak yang signifikan. Temuan ini memberikan wawasan yang dapat ditindaklanjuti bagi industri kosmetik halal, menekankan pentingnya pengembangan produk dan strategi pemasaran yang meningkatkan daya tarik emosional, menonjolkan manfaat fungsional, memanfaatkan pengaruh sosial, dan mengoptimalkan pemicu kondisional.